Pengaruh Academic Burnout terhadap Online Student Engagement pada Mahasiswa di Jawa Barat - Safira Mukhlisina; Sulisworo Kusdiyati (Bandung Conference Series: Psychology Science, 2023)
Abstract. Online learning is implemented in Indonesia due to the COVID-19 pandemic. The level of academic burnout for students is high during online learning during the COVID-19 pandemic. Student engagement is one of the important components needed in the learning process. Academic burnout has been shown to have a negative relationship with student engagement in previous studies. This study aims to investigate the effect of academic burnout on online student engagement on students in West Java. The method used is non-experimental causal research. The measuring instrument used is the Maslach Burnout Inventory-Student Survey (MBI-SS) by Schaufeli et al. and Online Student Engagement (OSE) by Dixson. The sample in this study amounted to 650 students in West Java who were selected through convenience sampling technique. The analysis used is simple linear regression analysis. The results of this study indicate that academic burnout can predict online student engagement negatively (significance value .-446) which means that each addition of one unit of academic burnout value will reduce online student engagement by .446. Academic burnout contributes to online student engagement by 12.1%. Keywords: Academic burnout, college student, online student engagement, Abstrak. Pembelajaran daring diberlakukan di Indonesia karena pandemi COVID-19. Tingkat academic burnout pada mahasiswa tinggi saat pembelajaran daring pada masa pandemi COVID-19. Student engagement adalah salah satu komponen penting yang diperlukan dalam proses pembelajaran. Academic burnout terbukti memiliki hubungan negatif dengan student engagement pada penelitian-penelitian terdahulu. Penelitian ini bertujuan untuk menyelidiki pengaruh academic burnout terhadap online student engagement pada mahasiswa di Jawa Barat. Metode yang digunakan adalah kausalitas noneksperimental. Alat ukur yang digunakan yaitu Maslach Burnout Inventory-Student Survey (MBI-SS) oleh Schaufeli et al. dan Online Student Engagement (OSE) oleh Dixson. Sampel dalam penelitian ini berjumlah 650 mahasiswa di Jawa Barat yang dipilih melalui teknik conveniece sampling. Analisis yang digunakan adalah analisis regresi linear sederhana. Hasil penelitian ini menunjukkan bahwa academic burnout dapat memprediksi online student engagement secara negatif (nilai signifikansi .-446) yang artinya setiap penambahan satu satuan nilai academic burnout akan menurunkan online student engagement sebesar .446. Academic burnout berkontribusi terhadap online student engagement sebesar 12.1%. Kata Kunci: Academic burnout, mahasiswa, online student engagement